STUDY ON THE WORKING CONDITION OF WOMEN WORKERS - GOVIND KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
The Millennial generation is now the portion of the modern workforce that is expanding at the quickest rate. Millennials in today's workforce are more interested in finding fruitful job options and career pathways that are tailored to their own goals and objectives. Jobs in the information technology sector are widely regarded as desirable employment opportunities among millennials in India today, particularly among millennial women. Taking into account the high amount of work and time that is demanded of employees, the constant connectivity of the workplace 24 hours a day, seven days a week, rapid technological change, and changes in the nature of work that have given rise to many employment issues, there has been an increased entry of millennial women into this sector, which has necessitated the need to achieve worklife compatibility. It is not uncommon for female millennial employees to feel pressured due to the increase in demand at work and personal life at the same time, making it difficult for them to manage their personal and professional responsibilities. This is especially true for employees who are millennials who are employed in the service industry. Therefore, finding a work-life balance has become a reality that is fraught with difficulty in today's unstable working environment. The immediate repercussions of work-life complications blur the boundaries between work and family life, and in the long term, this will have a substantial influence on the physical and psychological health of these millennial female workers. The purpose of this research is to investigate the issues that millennial women workers in the information technology industry have about the compatibility of their professional and personal lives. The current study's objectives are to examine the various work-life factors that influence the work-life compatibility of millennial women IT professionals, as well as to outline the work-life challenges that millennial women employees may face during the course of their employment, and to investigate the impact that this has on the organisation commitment and well being of millennial women employees during the different career stages of millennial women employees.